2001
DOI: 10.1177/104365960101200206
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Hope and Generic Caring Practices to Nurture Hope in a Rural Village in the Dominican Republic

Abstract: The purpose of this study was to explore the meaning of hope and generic caring practices to nurture hope among people of a rural village in the Dominican Republic. Ethnonursing methods were used to gather and analyze data from which a definition of hope for this group of people was developed: "Hope is an essential but dynamic life force that grows out of faith in God, is supported by relationships, resources and work, and results in the energy necessary to work for a desired future. Hope gives meaning and hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…During stressful experiences, women often seek affiliation with other members of their faith (Nosek & Hughes, 2001). In the Dominican Republic the concept of hope often is derived from one's faith in God and supported by relationships, resources, and work (Holt & Reeves, 2001). Thus, hope along with social support from family, friends, and fellow religious followers appear to give many women the power to transcend the conditions they face.…”
Section: Coping Processes and Strategiesmentioning
confidence: 98%
See 1 more Smart Citation
“…During stressful experiences, women often seek affiliation with other members of their faith (Nosek & Hughes, 2001). In the Dominican Republic the concept of hope often is derived from one's faith in God and supported by relationships, resources, and work (Holt & Reeves, 2001). Thus, hope along with social support from family, friends, and fellow religious followers appear to give many women the power to transcend the conditions they face.…”
Section: Coping Processes and Strategiesmentioning
confidence: 98%
“…Many women used hope as they continued to look to the future for a miracle. Previous research has suggested that the idea of hope is critical in the Dominican culture (Holt & Reeves, 2001).…”
Section: Coping Processes and Strategiesmentioning
confidence: 99%
“…The Hope Interview was created by Holt & Reeves (2001) to collect qualitative data. The question in this instrument consists of 2 big questions, question 1: What is your hope?…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…Hope can be fostered through relationships with others where support, guidance and trust are engendered. The importance of sustaining relationships in the facilitation of hope has been established in the literature (Holt, 2000;Holt & Reeves, 2001;Saleh & Brockopp, 2001;Seibaek et al, 2012). One inpatient and two home care nurses also described the relational aspects of hope.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…The power of hope through attributes such as future orientation, inner strength and endurance, the ever-present nature of hope, and the willpower to maintain hope through physical illness are themes identified by patients one year after sustaining a spinal cord injury (Lohne & Severinson, 2006). The meaning and importance of hope and caring practice to nurture hope for people in the Dominican Republic was explored using Leininger's four phase approach to conducting ethnographic research and analyzing data (Holt, 2000;Holt & Reeves, 2001). Themes abstracted from the data included hope as an essential life force, God as the primary source of hope, hope as supported by relationships, working together, economic resources and hard work, and hope resulting in energy, accomplishments, and happiness.…”
Section: Hope Qualified: Client Experiences With Hopementioning
confidence: 99%